Are stewardship and valuation usefulness compatible or alternative objectives of financial accounting? - Joachim Gassen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
In their joint framework project, the FASB and the IASB recently proposed dropping stewardship as a separate objective of financial accounting, because the Boards view stewardship and valuation usefulness as compatible sub-objectives ranking under an overall objective of decision usefulness. This paper puts this conjecture to an empirical test. As it is widely agreed that asymmetric timely earnings increase the contractual efficiency of accounting information, I first test whether firms with more asymmetric timely earnings produce more valuation-useful financial accounting information. Second, I test whether firms with more influential non-equity stakeholders provide more valuation-useful financial accounting information. As non-equity stakeholders in general face higher transaction costs when diversifying unsystematic risk compared to equity stakeholders and as stewardship-related risks should be at least in part unsystematic, I expect the demand for stewardship-related accounting information to increase with the influence of non-equity stakeholders. Using a broad sample of U.S. firms and a set of firm-specific metrics for valuation usefulness based on short-window capital market reactions to quarterly earnings announcements, I document that the valuation usefulness of financial accounting information is consistently negatively related to its stewardship-orientation. I conclude from these analyses that valuation usefulness and stewardship are alternative objectives of financial accounting.
Keywords: D82; G14; G34; M41; 330; decision usefulness; valuation usefulness; stewardship; conservatism; Bilanzierung; Informationswert; Bilanzielle Bewertung; Corporate Governance; Vergleich; International Financial Reporting Standards; USA